Abilities and barriers to practicing evidence-based nursing for burn specialist nurses. Issue 2 (March 2018) - Yue, Liqing; Fan, Xuegong; Peng, Huan
Highlights: Nurse's evidence-based nursing ability is positively correlated with the barriers to EBN, nurses' English proficiency level, research experiences and whether they are nurse educators. Only 3.4% of the nurses were familiar with EBN, 57.8% of nurses considered the need for EBN training. It is necessary to carry out targeted training and integrated management strategies to improve nurses' ability to EBN. Abstract: Objective: To explore the abilities and barriers of practicing evidence-based nursing (EBN) for burn specialist nurses so as to provide rationales for its clinical training and practice. Methods: From January 2016 to March 2016, a cross-sectional survey was conducted with a self-designed questionnaire among burn specialist nurses in Hunan Province. Data analysis was performed with SPSS software (version 20). Results: Burn specialist nurses in Hunan Province had diminished EBN abilities. The three procedures of EBN with the lowest score were "summarizing evidence through systematic reviews", "rigorous evaluations of evidence" and "systematic literature searches". And the three procedures of "clarifying problems", "disseminating evidence" and "introducing evidence" scored the highest. The systematic literature retrieval ability of nurses at class III general hospitals was higher than that of class II counterparts (P = 0.001). Thus EBN ability was positively correlated with barriers to practicing EBN, English proficiency, research experiences and educator status. Conclusion: Burn specialist nurses at classes III & II general hospitals in Hunan Province had poor EBN abilities. Influencing factors of EBN ability included barriers to practicing EBN, English proficiency, research experiences and educator status. Therefore it is imperative to implement targeted trainings and integrated managements for improved ability of practicing EBN.